The remission status before and the PCR status after high-dose therapy with peripheral blood stem cell support are prognostic factors for relapse-free survival in patients with follicular non-Hodgkin’s lymphoma - Moos, Marion; Schulz, Renate; Martin, Simona; Benner, Axel; Haas, Rainer (Leukemia, 1998)
It was the aim of our study to examine the clinical significance of t(14;18)-positive cells in samples from 47 patients with follicular non-Hodgkin’s lymphoma (NHL) who underwent high-dose therapy with autologous peripheral blood stem cell (PBSC) transplantation. At the time of PBSC mobilization, 25 patients were in first remission, while 22 patients had a history of previous treatment failure. At the same time, 43 patients had polymerase chain reaction (PCR)-positive cells in samples from bone marrow (BM) and/or peripheral blood (PB). Independent of the remission status, high-dose cytarabine and mitoxantrone with granulocyte colony-stimulating factor (G-CSF) support were administered for PBSC mobilization. Following high-dose conditioning therapy which consisted of cyclophosphamide (200 mg/kg) and hyperfractionated total body irradiation (TBI, 14.4 Gy) or BEAM (carmustine, etoposide, cytarabine, melphalan), 34 patients received PCR-positive and 13 patients received PCR-negative autografts. After a median follow-up time of 20 months (range, 6-50) post-transplantation, 33 patients were in remission, while 14 patients had relapsed after a median time of 14.5 months (range, 10-42). Using the Andersen-Gill proportional hazards regression model for the analysis of relapse-free survival, we found that PCR-positive findings in samples from BM and/or PB at any given time-point after transplantation were associated with an increased estimated hazard ratio of 4.5 in comparison with a PCR-negative finding (P = 0.013). On the other hand, patients included while they were in first remission had a smaller estimated hazard ratio of 0.3 when compared with patients with a history of previous treatment failure (P = 0.048). For the latter group of patients, this translates into a significantly smaller probability of relapse-free survival in comparison to patients who were in first remission at the time of PBSC-mobilization (P = 0.012). In conclusion, the remission status of the patients before autografting and the PCR status as assessed on the occasion of follow-up examinations are significant prognostic parameters for relapse-free survival in patients with follicular lymphoma undergoing high-dose therapy with PBSC autografting.
Gesehen am 14.05.2025